Book Review: From Natural Law to Political Economy: J.H.G. von Justi on State, Commerce and International Order by Ere Nokkala, Vienna, Lit Verlag, 2019, 312 pages. ISBN: 9783643910356 - Koskenniemi, Martti (Redescriptions : yearbook of political thought, conceptual history and feminist theory, 2020)
Teaching the skills of government specifically had been divided between theology and law in such a way that while the old literary genre of the mirror of princes was assigned to theologians, contemplating the virtues of a good ruler, lawyers were to teach the students about the origin and justification of state power, usually under Aristotelian constitutional categories. The science of government that was developed between Halle and Göttingen in the 18th century has sometimes been reduced to a history of the cameral sciences, but the scope of intellectual work was actually much wider and included subjects from the metaphysics of state power to principles of urban development, theories of just war to agricultural modernization, and from what was often called balance of trade to the fiscal techniques enabling the prince to live according to the expected level of ostentation. In due course, some it was integrated in administrative law in the 19th century, but most of the materials came to be treated in the novel discipline of Nationalökonomie or Staatswirstchaft.1 It was in this environment of intellectual and professional fermentation, with some academic disciplines on their way out, others struggling to get in, with the law school often thinking of itself as the queen of the sciences, that Johann H.G. Justi (1717–1771) entered in the 1750s and 1760s first in Vienna, then in Göttingen and eventually Berlin. Most of what Justi wrote was in the idiom of natural law, developing towards increasingly concrete and detailed instructions for the government of the various functions of the fiscal-military state, and this is also the starting point of Ere Nokkala’s insightful intellectual biography, although his interest is, understandably enough, on the contribution of his protagonist to what later was called political economy.